CC-CV Controlled Fast Charging Using Fuzzy Type-2 for Battery Lithium-Ion - Ahmad Zidan Falih; Mohammad Zaenal Efendi; Farid Dwi Murdianto (JAREE (Journal on Advanced Research in Electrical Engineering), 2021)
Energy dependency is increasing along with the increase in population growth rate, while the fossil energy is decreasing. Alternative energy such as solar energy is one solution to provide renewable energy, but solar energy cannot provide an intense supply of energy. Therefore, the equipment needs an energy storage. The battery has important role in energy storage with the performance of the battery that need an attention. The method and type of battery used  must be considered to maintain battery lifetime and  reduce overcharging. The purpose of this research is to understand the process of fast charging the CC-CV (Constant Current Constant Voltage) method on Lithium-Ion battery which is expected to reduce battery overcharging. In this method, the current is maintained constant until certain conditions then followed by constant voltage to prevent overcharging. The voltage from the solar panel is very high, voltage reduction is needed as the charging voltage for the battery. The DC-DC Converter used is Buck Converter which is given Fuzzy Type-2 algorithm to maintain a current of 10 Ampere during CC conditions and  a voltage of 14.4 Volt during CV conditions with switch of CC conditions to CV conditions on SoC 99.25%.Keywords: battery charging, buck converter, CC-CV, lithium-ion, type-2 fuzzy.